Technologies and virtual imaginary in the youth daily - Loayza Javier, Jerjes (2017)
The objective of this investigation is to analyze the consecuenques of social network use in the last five years, taking two different kinds of social mediators: Msn messenger and Facebook. For this, we describe the chat mechanisms, as a way of real time interaction, to deepen the ways in wich young people build new kinds of socialization using specialized codes. As distrust grows, the migration towards social networks where the users can demonstrate their existence with photographs and comments as is the case in Facebook or Wattsapp didn´t came as a surprise. These “nowhere places” are perceived as spaces of social islation that allow a virtual fantasy.